Altered Erythro-Myeloid Progenitor Cells Are Highly Expanded in Intensively Regenerating Hematopoiesis - Faltusová, Kateřina; Chen, Chia-Ling; Heizer, Tomáš; Báječný, Martin; Szikszai, Katarina; Páral, Petr; Savvulidi, Filipp; Renešová, Nicol; Nečas, Emanuel (Frontiers in Cell and Developmental Biology, 2020)
Regeneration of severely damaged adult tissues is currently only partially understood. Hematopoietic tissue provides a unique opportunity to study tissue regeneration due to its well established steady-state structure and function, easy accessibility, well established research methods, and the well-defined embryonic, fetal, and adult stages of development. Embryonic/fetal liver hematopoiesis and adult hematopoiesis recovering from damage share the need to expand populations of progenitors and stem cells in parallel with increasing production of mature blood cells. In the present study, we analyzed adult hematopoiesis in mice subjected to a submyeloablative dose (6 Gy) of gamma radiation and targeted the period of regeneration characterized by massive production of mature blood cells along with ongoing expansion of immature hematopoietic cells. We uncovered significantly expanded populations of developmentally advanced erythroid and myeloid progenitors with significantly altered immunophenotype. Their population expansion does not require erythropoietin stimulation but requires the SCF/c-Kit receptor signaling. Regenerating hematopoiesis significantly differs from the expanding hematopoiesis in the fetal liver but we find some similarities between the regenerating hematopoiesis and the early embryonic definitive hematopoiesis. These are in 1) the concomitant population expansion of myeloid progenitors and increasing production of myeloid blood cells 2) performing these tasks despite the severely reduced transplantation capacity of the hematopoietic tissues and 3) the expression of CD16/32 in most progenitors. Our data thus provide a novel insight into tissue regeneration by suggesting that cells other than stem cells and multipotent progenitors can be of fundamental importance for the rapid recovery of tissue function.